1982
DOI: 10.1111/j.1600-0609.1982.tb00586.x
|View full text |Cite
|
Sign up to set email alerts
|

A Family with Reduced Plasminogen Activator Activity in Blood Associated with Recurrent Venous Thrombosis

Abstract: 6 members of a family with a tendency to thrombosis and defective fibrinolysis were examined. After stimulation of plasminogen activator release from the vessel wall by local venous occlusion or by submaximal physical exercise, they had a lower plasminogen activator activity in blood than a healthy control group (P < 0.01). 5 of the examined members suffered from recurrent venous thrombosis. The defect appeared to be autosomal dominant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The risk of a permanent flow‐disrupting thrombus increases if this local regulation system is impaired. In support of this, several families with impaired capacity for t‐PA release have been reported to suffer from early‐onset, often recurrent, venous thrombosis . Furthermore, previous reports, including data from the Framingham Heart Study, have shown that genetically impaired t‐PA secretion causes a three‐fold increase in the adjusted risk for arterial thrombosis, i.e.…”
Section: Introductionmentioning
confidence: 78%
“…The risk of a permanent flow‐disrupting thrombus increases if this local regulation system is impaired. In support of this, several families with impaired capacity for t‐PA release have been reported to suffer from early‐onset, often recurrent, venous thrombosis . Furthermore, previous reports, including data from the Framingham Heart Study, have shown that genetically impaired t‐PA secretion causes a three‐fold increase in the adjusted risk for arterial thrombosis, i.e.…”
Section: Introductionmentioning
confidence: 78%
“…Several clinical studies have reported a possible association between defective fibrinolysis and TED (17). At least three families with TED were reported in which the affected members showed a defective release of t-PA activity after venous occlusion of the arm and/or intravenous infusion of DDAVP (18)(19)(20). It was shown recently that poor fibrinolytic response to venous occlusion occurred in 35% of patients with deep vein deep vein thrombosis and 10% was due to deficient t-PA release (9,21).…”
Section: Discussionmentioning
confidence: 99%
“…A study has reported that rare deleterious genetic variations in PLAT may be associated with prolonged illness duration and poorer prognosis in patients with early onset of Alzheimer's disease 19 . Several earlier papers highlighted the association of familial defects in tPA release with venous thromboembolic events 20,21 . However, in the context of thrombophilia, pathogenetic mutations in PLAT have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Several earlier papers highlighted the association of familial defects in tPA release with venous thromboembolic events. 20 , 21 However, in the context of thrombophilia, pathogenetic mutations in PLAT have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%